2015
DOI: 10.1007/s13346-015-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal deployment and tenofovir delivery by microbicide gels

Abstract: Gels are one of the soft material platforms being evaluated to deliver topically acting anti-HIV drugs (microbicides) to the vaginal environment. For each drug, its loaded concentration, gel properties and applied volume, and frequency of dosing can be designed to optimize PK and, thence, PD. These factors also impact user sensory perceptions and acceptability. Deterministic compartmental modeling of vaginal deployment and drug delivery achieved by test gels can help delineate how multiple parameters character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 38 publications
0
56
0
Order By: Relevance
“…The DuoGel™ formulations developed were composed of excipients either listed in the FDA Inactive Ingredients Database (http://www.accessdata.fda.gov/scripts/cder/iig/index.cfm) as accepted excipients in vaginal products, rectal products, or already used in over the counter products. The TPP viscosity of the DuoGel™ was initially defined at 120 Pa·s at 1 sec −1 shear stress in order to provide sufficient gel coverage in the vagina and rectum without causing leakage (Gao et al ., 2015). The DuoGel™ TPP pH of 6.1 was based on achieving a compromise value that does not harmfully perturb ambient conditions in the vagina or rectum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DuoGel™ formulations developed were composed of excipients either listed in the FDA Inactive Ingredients Database (http://www.accessdata.fda.gov/scripts/cder/iig/index.cfm) as accepted excipients in vaginal products, rectal products, or already used in over the counter products. The TPP viscosity of the DuoGel™ was initially defined at 120 Pa·s at 1 sec −1 shear stress in order to provide sufficient gel coverage in the vagina and rectum without causing leakage (Gao et al ., 2015). The DuoGel™ TPP pH of 6.1 was based on achieving a compromise value that does not harmfully perturb ambient conditions in the vagina or rectum.…”
Section: Resultsmentioning
confidence: 99%
“…From the onset of formulation development of the DuoGel™, a range of gel viscosities was chosen, from relatively “low” (IQB3001) to “high” (IQB3000), to vary the rate and extent of gel spreading (Gao et al ., 2015; Kieweg and Katz, 2006). As per the TPP, the gels were manufactured to have a point viscosity (@ 1 s −1 ) of less than 120 Pa·s (Ham et al ., 2012; Mahalingam et al ., 2011; Rohan et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy to highly active antiretroviral therapy (HAART), a combination of ARV agents likely is essential for optimally effective HIV PrEP (1,2). Multiple HIV PrEP clinical trials have demonstrated that vaginal and oral ARV regimens based on the nucleoside reverse transcriptase inhibitor (NRTI) tenofovir (TFV) can be effective in susceptible men, women, and partners of HIV-infected individuals (3)(4)(5)(6)(7)(8)(9), but other studies based on analogous drug regimens were unsuccessful at reducing the rates of HIV acquisition (10)(11)(12). A critical factor driving success in these trials appears to involve sustaining high adherence to frequent dosing (13).…”
mentioning
confidence: 99%
“…The product retention in the vagina and rectum will depend on the physical state. For liquid and semisolid preparations, product viscosity and the administered volume are important attributes that dictate leakage from and spreading within the vaginal and rectal compartments [30, 31]. For solid dosage forms such as vaginal tablets, inserts, suppositories, and films, disintegration will impact drug delivered to the mucosal site.…”
Section: Design Considerations For On-demand Productsmentioning
confidence: 99%